(untitled) (Foro de Educacion, 2015)
The principles, values and goals of education for sustainable development inspire this monographic, which is aligned with the educational proposals of the United Nations post-2015 global development agenda. It is composed of eleven articles, submitted from Cuba, Finland, Spain and Mexico. After a first text of a more theoretical nature, the following ten authors address different issues of the teaching practice oriented towards the building of essential competencies to shape societies characterized by the sustainability of their development. In this brief introduction, the objective is to provide the general framework and lay down the connections between the articles accepted by the reviewers for the publication in the monographic. The special issue is finished with a conversation between two know experts in the field, who put in common their points of view on the educational challenge presented by this new sociocultural model.